2019
DOI: 10.1021/acs.jproteome.9b00261
|View full text |Cite
|
Sign up to set email alerts
|

MMP-2 and MMP-9 in Human Peripheral Blood: Optimizing Gelatinase Calibrator for Degradome Research and Discovering a Novel Gelatinolytic Enzyme

Abstract: Matrix metalloprotease-2 and -9 (gelatinase A and B, respectively) are enzymes crucially involved in a plethora of physiopathological conditions. Gelatin zymography is considered one of the major qualitative/semiquantitative assays for simultaneously determining zymogenic, active, and complexed forms of gelatinases. Critical steps are represented by variations in sample collection methods, molecular weight standard calibrators, and different zymography assay protocols. A normalization of these aspects is requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
(106 reference statements)
0
10
0
Order By: Relevance
“…These findings are similar to our results. In addition, gelatinases A and B, namely matrix metalloproteinases 2 and 9, were reported to be synthesized and secreted in vivo as latent pro-enzymes with molecular weights between 72-225 kDa [23]. Therefore, there might also be some precursor enzymes in the extracts of sea cucumber intestines in this study.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…These findings are similar to our results. In addition, gelatinases A and B, namely matrix metalloproteinases 2 and 9, were reported to be synthesized and secreted in vivo as latent pro-enzymes with molecular weights between 72-225 kDa [23]. Therefore, there might also be some precursor enzymes in the extracts of sea cucumber intestines in this study.…”
Section: Discussionmentioning
confidence: 72%
“…Weak bands were observed at around 133 kDa. This may be due to polymers or precursors of some enzymes [23].…”
Section: Optimal Conditions Of Gelatinolytic Enzymes In Sea Cucumber ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In order to further study the possible process of collagen degradation in membranes, MMP9 was detected by immunohistochemistry. MMP9 belongs to the matrix metalloproteinases family and is a kind of gelatinase [ 35 , 36 ]. Our study found that the expression of MMP9 in our antimicrobial membrane was high, which indicated that the collagen fiber was degraded and the biocompatibility was good.…”
Section: Discussionmentioning
confidence: 99%
“…The lysed supernatants were quantified using Bradford method and 16.6 μg of total proteins were loaded in each lane. Gelatin zymography was carried out with fixed-concentration (7.5%) polyacrylamide separating gels copolymerized with 3 g/L 90 Bloom Type A gelatin and 4% stacking gel as described previously [ 27 ]. Briefly, zymogram gels were run in cold SDS running buffer (25 mM Tris, 192 mM glycine, and 0.1% w/v SDS) at a constant voltage of 120 V, for about 2 h. After electrophoresis, gels were washed twice for 20 min at room temperature in Triton X-100 2.5% to gently remove SDS.…”
Section: Methodsmentioning
confidence: 99%